Regulating bank risk in a mobile labour market - van Boxtel, Anton (Journal of Banking & Finance, 2025)
This paper argues that bonus caps can be welfare improving in banking labour markets with high mobility. On the labour market, the largest banks hire the most talented traders, but they need to do so with contracts with high bonuses in order to both screen talent and to prevent poaching by smaller banks. This can lead to excessive risk taking. In some cases, it is socially optimal to prevent screening, leading to a less efficient matching of talent to banks, but also to less risk taking. Bonus caps can achieve this in a way that is both more effective and less costly than setting tighter capital constraints.